2015
DOI: 10.1016/j.bbi.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Negative affectivity predicts decreased pain tolerance during low-grade inflammation in healthy women

Abstract: NA moderated the effects of inflammation on pain tolerance. This finding is consistent with a synergistic model whereby inflammation may lower the threshold for pain reporting in individuals with increased vulnerability for somatic symptom reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
(38 reference statements)
0
24
0
Order By: Relevance
“…Indeed, inflammation is a hallmark of ageing and replication of results to such a relevant group is advised. Moreover, even thoughLacourt et al, (2015) showed that vaccination does not affect pain tolerance or pain threshold and no side effects were reported in the current study, pain could have influenced performance and lack of assessing pain is a limitation of the study. Similarly, even though modified versions of the Profile of Mood Scales-Short Form (POMS-SF) have been used extensively in typhoid vaccination studies (e.g.,Brydon et al, 2009;, the use of a modified POMS-SF to measure mood and sickness can be considered as a limitation of…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Indeed, inflammation is a hallmark of ageing and replication of results to such a relevant group is advised. Moreover, even thoughLacourt et al, (2015) showed that vaccination does not affect pain tolerance or pain threshold and no side effects were reported in the current study, pain could have influenced performance and lack of assessing pain is a limitation of the study. Similarly, even though modified versions of the Profile of Mood Scales-Short Form (POMS-SF) have been used extensively in typhoid vaccination studies (e.g.,Brydon et al, 2009;, the use of a modified POMS-SF to measure mood and sickness can be considered as a limitation of…”
mentioning
confidence: 59%
“…Such alternative is provided by inflammation-induction through vaccination against Salmonella typhi (the causal agent of typhoid fever). Vaccination likewise reliably initiates an acute systemic inflammatory response, lasting up to 12 hours, but without generating flu-like symptoms Lacourt et al, 2015;Paine, Ring, Bosch, Drayson, & Veldhuijzen van Zanten, 2013 but also Harrison et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we could observe that pregnant women presented similar glucose and total cholesterol levels [25][26][27] ; and greater LDL and HDL-cholesterol, 25,27 and triglycerides concentrations. 25 Regarding the inflammatory markers, pregnant women showed higher levels of IL-1, 28 IL-6, 25-29 IL-8, 28 IL-10, 28 IFN-γ, 28 and TNF-α 25,27,29 than non-pregnant women of similar characteristics. These comparisons and previous evidence 1,6,30,31 seem to support the idea that early pregnant women are predisposed to a mild pro-inflammatory profile, despite the fact that changes on cardiometabolic markers are not very accentuated.…”
Section: Discussionmentioning
confidence: 98%
“…The physical examination and medical history allowed for assessment of chronic conditions that are characterized by musculoskeletal pain (e.g., arthritis) and abnormal joints or musculature that could might result in increased numbers of tender points. Elevated peripheral inflammation has previously been associated with increased pain sensitivity both under basal conditions 38 , and during experimentally induced inflammation with immunogenic challenges 70 an effect that may be mediated by increases in negative affective processes 34 . Sympathetic nervous system activation measured by urinary catecholamine (as in the MIDUS study) has also been linked to increased reports of musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%